Financing the U.S. deficit: adjustment mechanics between the U.S. and Japan - Qian, Shenglin, author; Vasudevan, Ramaa, advisor; Koontz, Stephen R., committee member; Braunstein, Elissa, committee member (Colorado State University. Libraries, 2009)
Japan has run a large trade surplus with the U.S. and has financed the U.S. deficit for a long time, so the adjustment mechanism of financial flows between the U.S. and Japan is an important issue. In this paper, in order to investigate the capital flow between Japan and the U.S, I build a VAR model to study the fluctuations of interest rate spread between the U.S. and Japan and international reserve of Japan. The analysis of the Impulse Response Function suggests that the dynamic response to an event, such as the rise of the deficit of the U.S. is such that movements in the international reserve of Japan and the interest rate spread tend to restore equilibrium. To support my conclusion, I use the subset of the sample data to simulate and forecast the real event. The work shows that the model can accurately explain the adjustment process.
Covers not scanned.
Keywords: Foreign exchange rates -- Japan -- Mathematical models; Foreign exchange rates -- United States -- Mathematical models; Deficit financing -- United States